Luba and the wren - Polacco, Patricia (New York : Puffin Books, 2002)
In this variation on the story of "The Fisherman and His Wife," a young Ukrainian girl must repeatedly return to the wren she has rescued to relay her parents' increasingly greedy demands.
Wilson's Children
School Library Journal
Publisher's Weekly
3.9
K-3
Keywords: Fairy tales; Folklore -- Russia; Folklore -- Ukraine; Fairy tales; Folklore -- Russia; Folklore -- Ukraine